Hubungan Aktivitas Fisik dengan Tingkat Stres dan Kecemasan pada Day Traders Indonesia - Purnama, Depi; Kusnaedi, Kusnaedi; Ramania, Nia Sri (Institut Teknologi Bandung, 2023)
Since the COVID-19 pandemic, public interest in day trading on the stock exchange has increased significantly. Day trading promises early profits and the opportunities of it everyday. Unfortunately, this scope has the potential to increase sedentary behavior and mental health disorders associated with stress and anxiety. To deal with those risks, as known that physical activity is a protective factor for the prevention and management of health problems due to sedentary activity. Physical activity is also beneficial for mental health and general well-being. The purpose of this study is to analyze the level of physical activity, the level of stress and anxiety, and the correlation between physical activity and stress and anxiety levels among day traders in Indonesia. Correlational analysis with cross-sectional design has been used as research method this study. The International Physical Activity Questionnaire – Short Form (IPAQ-SF) and Depression Anxiety and Stress Scale (DASS-21) instruments were used as data collection tools which were distributed online to the trader community in Indonesia (n = 392). Statistical test results with Rank Spearman showed a significance value between physical activity and stress level of 0.000 (p<0.05), and between physical activity and anxiety level of 0.000 (p<0.05), this result indicating the correlation between physical activity and stress and anxiety levels. The subjects who have a low level of physical activity are as many as 33.67%, moderate physical activity 40.56%, and high physical activity 25.77%. Most of the subjects had a normal stress level of 68.62%. By the same token, the level of anxiety, the average has a normal anxiety level of 51.28%. The subjects with high levels of physical activity had lower levels of stress and anxiety, and the subjects with screen time duration of ≥ 4 hours had more severe levels of stress and anxiety. From these research findings, the recommendation of maximum duration of screen time trading is only 4 hours per day, and it is recommended for traders to perform physical activities such as stretching during day trading activities.